Wady wrodzoneLong-term results after extracardiac total cavopulmonary connection - Kansy, Andrzej; Maruszewski, Bohdan; Mirkowicz-Małek, Małgorzata; Kościesza, Andrzej; Dmeńska, Hanna; Kwaśniak, Ewelina; Burczyński, Piotr; Brzezińska-Rajszys, Grażyna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: Extracardiac TCPC provides laminar blood flow, reduces atrial wall tension and reduces the possibility of dysrhythmia. The aim of the study was to evaluate long-term results in 27 patients after extracardiac TCPC operated on between 1992 and 2002 for various forms of functionally single ventricle. Material and methods: 31 extracardiac TCPC were performed. Age at operation was 7.6, 95% CI (6.2–8.9), SD 3.7. Body weight 20.7, 95% CI (18.3–23.2), SD 6.7. Pre-op diagnoses were: TA – 12, DILV 7, DORV – 6, Heterotaxy – 3, other – 3. There were 12 direct IVC – P-A anastomoses and 19 interposed conduits (13 aortic allografts, 6 PTFE grafts). Early survival was 90.3% (28/31). At mean follow-up of 7.4 years, 95%CI (6.4–8.5), SD 2.7 all patients underwent: physical examination, CXR, ECG, ECHO, spiral CT scan and spirometry. Results: Somatic growth was normal (b.w. 34.8, 95%CI (22.6–47.1), height 34.8, 95% CI (22.5–47.1) percentile). O2 sat. 93.8, 95%CI (92–95), SD 2.9. McGoon ratio was 1.6, 95% CI (1.5–1.8), SD 0.3 and dropped from 2.3, 95% CI (2–2.5), SD 0.6 at surgery. %EF 75.5, 95% CI (72.1–78.9), SD 7.8. No pressure gradient across the TCPC anastomoses was found. The loss of graft diameter was less in the allograft group (10%) than in PTFE (20%). No reoperation was required. 3 patients are paced (2 since before surgery); all others remain in sinus rhythm. Spirometry showed normal total lung capacity (TLC-He) and CO transfer factor (TLCO) in 90% of patients. Conclusions: Extracardiac TCPC provides very good long-term anatomical and functional outcome. Direct cavo-pulmonary connection was feasible in 38.7%. Our conduit of choice is non-valved cryopreserved ascending aorta allograft.